A-175 Personality as a Proxy for Positive Effort: The Role of Grit, Need for Cognition, and Extraversion in Problem-Solving. (30th August 2021) - Hawley, Nanako A; Myers, Melissa; Pizer, Jasmin; Harrell, Murphy; Hill, Benjamin D
Abstract: Objective: This study aimed to examine the effect of personality traits on a simple problem-solving test of intelligence. Method: The sample consisted of 82 undergraduates. Participants completed an online battery that included an open source Five Factor Model measure (IPIP FFM), Grit scale, Need for Cognition (NFC) scale, and the Cognitive Reflection Test (CRT). CRT is a simple 3 question test of intelligence. An interaction variable for positive effort was created by multiplying the total raw scores for the Grit and NFC scales (Grit x NFC). Correlations were conducted between the Grit x NFC, IPIP FFM, and the CRT total score. Scales that significantly correlated with CRT total score were entered into a regression model. Results: Pearson correlations revealed a significant positive association between Grit x NFC and CRT performance, (r = 0.240, p < 0.05). A significant correlation was also found between IPIP FFM Extraversion factor and CRT performance (r = 0.230, p < 0.05). A regression model found that Grit x NFC and IPIP FFM Extraversion accounted for 9.2% of the variance in CRT total scores, (R2 = 0.092, F(1, 82) = 3.92, p = 0.024). When examined individually, no individual predictors were significant. Conclusion: These findings suggest that personality traits that reflect positive effort such as Grit and NFC as well as other personality features influence performance on problem-solving bases measures of intelligence. Future research should examine these findings in a larger sample with a broader array of cognitive measures to quantify the role of positive effort in cognitive performance.